RNAi-Based Functional Genomics in Hemiptera - Ritesh G. Jain; Karl E. Robinson; Stephen J. Fletcher; Neena Mitter (Insects, 2020)
RNA interference (RNAi) is a powerful approach for sequence-specific gene silencing, displaying tremendous potential for functional genomics studies in hemipteran insects. Exploiting RNAi allows the biological roles of critical genes to be defined and aids the development of RNAi-based biopesticides. In this review, we provide context to the rapidly expanding field of RNAi-based functional genomics studies in hemipteran insects. We highlight the most widely used RNAi delivery strategies, including microinjection, oral ingestion and topical application. Additionally, we discuss the key variables affecting RNAi efficacy in hemipteran insects, including insect life-stage, gene selection, the presence of nucleases, and the role of core RNAi machinery. In conclusion, we summarise the application of RNAi in functional genomics studies in Hemiptera, focusing on genes involved in reproduction, behaviour, metabolism, immunity and chemical resistance across 33 species belonging to 14 families.